Behavioral Parameters of Planarians (Girardia tigrina) as Fast Screening, Integrative and Cumulative Biomarkers of Environmental Contamination: Preliminary Results - Córdova López, Ana M. (2021)
The present study aims to use behavioral responses of the freshwater planarian Girardia tigrina to assess the impact of anthropogenic activities on the aquatic ecosystem of the watershed Araguaia-Tocantins (Tocantins, Brazil). Behavioral responses are integrative and cumulative tools that reflect changes in energy allocation in organisms. Thus, feeding rate and locomotion velocity (pLMV) were determined to assess the effects induced by the laboratory exposure of adult planarians to water samples collected in the region of Tocantins-Araguaia, identifying the sampling points affected by contaminants. Furthermore, physicochemical and microbiological parameters, as well as the presence of inorganic compounds (dissolved aluminum, total barium, total chloride, dissolved iron, total fluoride, total manganese, nitrates, nitric nitrogen, total sulfate, total zinc) and surfactants, were determined on each specific sampling point. The behavioral biomarkers (feeding rate and pLMV) of the freshwater planarians were significantly decreased when organisms were exposed to water samples from four municipalities (Formoso do Araguaia, Lagoa da Confusão, Gurupi and Porto Nacional), sites of the Tocantins-Araguaia hydrographic region—TAHR. Both behavioral biomarkers decreased up to ~37–39% compared to organisms in ASTM medium only. Our results showed that these behavioral biomarkers can be used for fast screening monitoring of environmental samples of freshwater ecosystems, since a decrease in feeding rate and locomotor activity was observed in sites impacted by anthropogenic activities. However, the absence of effects observed in some sampling points does not represent the absence of contamination, since several other classes of contaminants were not determined. In these negative results, the absence of deleterious effects on behavioral biomarkers might only be indicative that the potential presence of contaminants on such sites does not significantly affect the performance of planarians. This fast screening approach seems to be useful to determine contaminated sites in freshwater ecosystems for biomonitoring purposes. This knowledge will help to develop biomonitoring programs and to decide appropriate sampling sites and analysis.